Sex-based differences in the activation of peripheral blood monocytes in early Parkinson disease - Carlisle, Samantha M.; Qin, Hongwei; Hendrickson, R. Curtis; Muwanguzi, Jordana E.; Lefkowitz, Elliot J.; Kennedy, Richard E.; Yan, Zhaoqi; Yacoubian, Talene A.; Benveniste, Etty N.; West, Andrew B.; Harms, Ashley S.; Standaert, David G. (NPJ Parkinson's Disease, 2021)
Increasing evidence supports the role of brain and systemic inflammation in the etiology of Parkinson disease (PD). We used gene expression profiling to examine the activation state of peripheral blood monocytes in 18 patients with early, untreated PD and 16 healthy control (HC) subjects. Monocytes were isolated by negative selection, and gene expression studied by RNA-seq and gene set enrichment analysis. A computational model that incorporated case/control status, sex, and the interaction between case/control status and sex was utilized. We found that there was a striking effect of sex on monocyte gene expression. There was inflammatory activation of monocytes in females with PD, with enrichment of gene sets associated with interferon gamma stimulation. In males, the activation patterns were more heterogeneous. These data point to the importance of systemic monocyte activation in PD, and the importance of studies which examine the differential effects of sex on pathophysiology of the disease.